(untitled) (Bangladesh Journal of Obstetrics & Gynaecology, 2023)
Vaginal cancer, rarest form of gynaecological cancer (0.6%) has been found to be associated with long term use of vaginal ring pessary, which have long been used in alternative management of pelvic organ prolapse (POP) other than surgery. A through survey was done in remote areas of Cox’s bazar, refugee camp where out of 52 cases of pelvic organ prolapse, 7 cases found to use vaginal ring pessary for long and out of 7, vaginal cancer developed in 4 cases. All of them were aged women above 60 and had defaulted follow up presented with vaginal bleeding, varying discharge and pain of varying intensity. One patient had only local lesion was treated by surgical removal followed by radiotherapy. The 2 nd one, 68 years, received neo-adjuvant therapy and died before planned surgery. The 3 rd one, aged 79, did not come for follow up after diagnosis of vaginal cancer done and advised for definitive surgical treatment, family refused operation and she passed away after 2 years at 81 years. The 4 th one declined further investigations and any form of treatment once diagnosed with vaginal cancer. So, all patients of pelvic organ prolapse should be informed thoroughly (both verbal and written informed consent) before inserting pessary for potential long term serious consequences where strict compliance must be ensured for subsequent regular follow up and biopsy should be mandatory for any suspicious chronic vaginal ulcers among them. Bangladesh J Obstet Gynaecol, 2022; Vol. 37(1): 75-77